2018
DOI: 10.1002/anie.201713391
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an Eleven‐Atom Polydentate Carbon‐Chain Chelate Obtained by Cycloaddition of a Cyclic Osmium Carbyne with an Alkyne

Abstract: Carbon ligands have long played an important role in organometallic chemistry. However, previous examples of all-carbon chelating ligands are limited. Herein, we present a novel complex with an eleven-atom carbon chain as a polydentate chelating ligand. This species was formed by the [2+2+2] cycloaddition reaction of two equivalents of an alkyne with an osmapentalyne that contains the smallest carbyne bond angle (127.9°) ever observed. Density functional calculations revealed that electron-donating groups play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 76 publications
1
28
0
Order By: Relevance
“…4), a series of reactant osmapentalynes (1b-1g) were synthesized by the treatment of carbon ligands (L2-L7) with multiyne chains with OsCl 2 (PPh 3 ) 3 and PPh 3 , the different substituents at different positions appear not to affect the reaction (3,(31)(32)(33)(34)(35)(36). For instance, the R′ substituent can be styryl (3), phenyl (31)(32)(33), thienyl (34) or hydrogen (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46), and the Y group can be CH 2 (31,34), O (32,35) or C(COOMe) 2 (33,36). The structures of all the above complexes were confirmed by NMR spectroscopy, EA and HRMS ( Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4), a series of reactant osmapentalynes (1b-1g) were synthesized by the treatment of carbon ligands (L2-L7) with multiyne chains with OsCl 2 (PPh 3 ) 3 and PPh 3 , the different substituents at different positions appear not to affect the reaction (3,(31)(32)(33)(34)(35)(36). For instance, the R′ substituent can be styryl (3), phenyl (31)(32)(33), thienyl (34) or hydrogen (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46), and the Y group can be CH 2 (31,34), O (32,35) or C(COOMe) 2 (33,36). The structures of all the above complexes were confirmed by NMR spectroscopy, EA and HRMS ( Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The high ring strain associated with this small carbyne angle promoted us to investigate the reactivity of 1a and 2a with alkynes. In our previous work, only cycloaddition reactions based on similar osmapentalyne complexes were reported 27 , 30 , 31 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The metal-carbon triple bond possesses an "alkyne-like" character and can react with an external metal precursor to generate bimetallic adducts, in which osmium-carbon triple bond coordinated with the coinage metal center. Xia reported that osmapentalyne 44 [48] was treated with cuprous chloride to afford hetero bimetallic adduct 45, in which the chloride bonded to osmium also coordinated with copper atoms. As different silver or gold precursors were subjected to osmapentalyne 44, the corresponding hetero bimetallic adduct 46 or 47 was formed in a similar way.…”
Section: Formation Of Osmapentalyne-coinage Metal Complexesmentioning
confidence: 99%
“…Recently, Xia and coworkers documented a series of five-membered cyclic metal carbyne complexes, i.e., osmapentalynes [47][48][49][50][51] and ruthenapentalynes [52]. The carbine-carbon bond angles in the metallapentalynes are around 130 • , which are much smaller than those of the acyclic metal carbynes (180 • ).…”
Section: Reactivity Of Five-membered Metallapentalynesmentioning
confidence: 99%